Highly diastereoselective anti-dihydroxylation of 3-N,N-dibenzylaminocyclohex-1-ene N-oxide. - Aciro, C; Davies, S; Kurosawa, W; Roberts, P; Russell, A; Thomson, J (2009)
Oxidation of 3-N,N-dibenzylaminocyclohex-1-ene N-oxide in the presence of Cl3CCO2H proceeds with high levels of anti-diastereoselectivity (97% de), with no competing side reactions, allowing access to 1,2-anti-2,3-anti-3-aminocyclohexane-1,2-diol after deprotection.